2011
DOI: 10.1063/1.3567910
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystal polarity on crystal defects in GaP grown on exact Si (001)

Abstract: For the implementation of optoelectronic devices on silicon, which could be realized by a combination of Si and direct-bandgap III/V semiconductors, a defect free nucleation layer of GaP on Si is essential. This paper summarizes the results of structural investigations carried out by transmission electron microscopy on defects, which can be observed in GaP films grown by metal organic vapor phase epitaxy on exactly oriented (001) Si substrates. Under optimized growth conditions the anti phase domains (APDs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 21 publications
3
68
0
Order By: Relevance
“…9 intersect the ELOG layer surface in the [110] direction, the fault must lie either on a (111) plane or a (1-11) plane; whichever it may be, it does not alter the model due to symmetry. investigation, and a similar SF polarity has been observed in other heteroepitaxial systems such as GaP on Si [27].…”
Section: Resultssupporting
confidence: 52%
“…9 intersect the ELOG layer surface in the [110] direction, the fault must lie either on a (111) plane or a (1-11) plane; whichever it may be, it does not alter the model due to symmetry. investigation, and a similar SF polarity has been observed in other heteroepitaxial systems such as GaP on Si [27].…”
Section: Resultssupporting
confidence: 52%
“…In addition to showing the preferential annihilation of APBs along {112} planes [30], Beyer et al, observed that in similarly grown GaP-on-Si samples APBs oriented along {110} planes displayed a tendency to jump one or more atomic planes, thereby creating a finite thickness to the APB [31]. Thus, increasing growth temperature can increase the jump probability for APB planes and enhance the annihilation rate.…”
Section: Resultsmentioning
confidence: 95%
“…It will be reported elsewhere [38] that the APBs which kink on {1 1 1} or {1 1 2} planes can consist of P-P false bonds. Therefore, the V/III ratio used during overgrowth might play a role in the kinking of the APBs.…”
Section: Influence Of V/iii Ratiomentioning
confidence: 97%
“…Therefore, specific care should be taken when judging defects from cross-sectional TEM investigations, as one need to choose the proper /1 1 0S direction for preparation to image these defects. A detailed investigation of the polarity of the GaP layers deposited on Si and its dependence on growth conditions, as well as of the defects which are formed in these layers and their dependence on the crystal polarity, will be published elsewhere [38].…”
Section: Annealing Of the Homoepitaxial Si-buffer: Influence Of Si Sumentioning
confidence: 99%